Nurses' Attitudes Towards the Implementation of Atraumatic Care for Hospitalized Children: A Hospital Based Study in Kenya - ROTICH, Brigid (East African Journal of Nursing, 2025)
Hospitalization can be distressing for children, often resulting in psychological and emotional strain. Atraumatic care aims to minimize these effects by fostering a child-friendly environment, reducing pain, and promoting family involvement. As the primary caregivers, nurses play a pivotal role in actualizing these principles, and their attitudes significantly influence the quality and consistency of atraumatic care delivery. This study assessed the attitudes of nurses toward the implementation of atraumatic care for hospitalized children at Nakuru Level-5 Hospital in Kenya. A descriptive cross-sectional design was adopted. The study was conducted at Nakuru Level-5 Hospital, a major referral facility in Kenya’s Rift Valley. The target population included nurses working in the pediatric ward with a minimum of three months of continuous service. A total of 48 nurses were selected using purposive sampling. Data were collected using a structured, self-administered questionnaire designed to measure attitudes related to key aspects of atraumatic care. Descriptive statistics were used for data analysis using SPSS version 25. The majority of respondents (77%) agreed that parental involvement enhances atraumatic care, and 73% viewed atraumatic care as influenced by personal belief systems. Most nurses (77%) reported awareness and implementation of non-pharmacologic pain management methods, while 72.9% rated themselves as very or extremely confident in communicating with pediatric patients to reduce anxiety. Despite these positive attitudes, a minority of nurses expressed disagreement or uncertainty, indicating areas where additional support may be required. While overall attitudes toward atraumatic care were favorable, variations in belief, awareness, and confidence highlight the need for further reinforcement of trauma-informed care principles. Healthcare facilities should institutionalize continuous training and mentorship programs to strengthen nurses' attitudes and competencies in child-centered, trauma-informed care.